PEMIKIRAN MODERNIS MUHAMMAD IQBAL DAN FAZLUR RAHMAN DALAM PENDIDIKAN ISLAM - Shiddqi Junaidi; Farham; Matroni (Kariman: Jurnal Pendidikan Keislaman, 2022)
This is the philosophical view of Sir Muhammad Iqbal and the modernist view of Fazlur Rahman in his thoughts on Islamic education. This is a descriptive qualitative research that describes the philosophical and Modernist views of Islamic education according to Iqbal and Fazlur Rahman. The results of the study, that the philosophical and modernist views of the two main ideas about Islamic education, are how to create Insan Kamil (perfect humans). Insan Kamil must be the main goal and primary education. According to Iqbal, there are eight main ideas to reconstruct Islamic education philosophically by increasing human dynamics and creativity. While the thought of modernizing Islamic education is interesting and has a considerable effect on the renewal of Islamic education, namely Fazlur Rahman. In his thinking, he wants the Muslim community to have a great contribution in developing science and not be defensive. In addition, he wants a combination of secular education with Islamic teachings, the steps taken are assimilation between education and Islamic values.